Comparisons of histological features among primary oral squamous cell carcinomas before and after adjuvant chemotherapy and their lymph node metastatic cancer lesions after adjuvant chemotherapy - Feng-Chou Cheng; Ling-Hsia Wang; Yi-Ping Wang; Julia Yu-Fong Chang; Chun-Pin Chiang (Elsevier, 2022)
Background/purpose: Adjuvant chemotherapy has been used to control the primary oral squamous cell carcinoma (OSCC) size prior to surgical excision of the cancer. This study aimed to explore the histological changes of primary OSCCs and their cervical lymph node metastatic cancer lesions after chemotherapy. Materials and methods: Thirty-three OSCC patients with eleven having cervical lymph node metastases received adjuvant chemotherapy before surgical excision of their cancer lesions. Hematoxylin and eosin-stained tissue sections of incisional biopsy, surgical excision, and cervical lymph node metastatic cancer lesion specimens were compared microscopically to observe the histological changes in the cancer tissues after chemotherapy. Results: Common histological features could be found in the primary OSCCs and their cervical lymph node metastatic cancer lesions after chemotherapy. These included direct killing of cancer cells by chemotherapeutic agents, resulting in cancer cell necrosis and degeneration in the early phase, and squamous and keratinizing metaplasia of drug-induced cancer cells, leading to individual cell keratinization and keratin pearl formation in the later phase. There were also small nests of drug-resistant proliferating cancer cells in the inflamed fibrous connective tissue stroma. The most characteristic histological feature in the metastatic lymph nodes after chemotherapy was the keratinizing metaplasia of the metastatic cancer cells, resulting in the formation of epidermoid cyst-like lesions. Conclusion: Although the cancer reduces its size after chemotherapy, residual cancer cells are consistently present in the primary OSCC lesions after chemotherapy. Therefore, wide surgical resection of the cancer is still needed to ensure the complete removal of all cancer tissues.